Chagas Disease: From Discovery to a Worldwide Health Problem - Lidani, Kárita Cláudia Freitas; Andrade, Fabiana Antunes; Bavia, Lorena; Damasceno, Flávia Silva; Beltrame, Marcia Holsbach; Messias-Reason, Iara J.; Sandri, Thaisa Lucas (Frontiers in Public Health, 2019)
Carlos Chagas discovered American trypanosomiasis, also named Chagas disease (CD) in his honor, just over a century ago. He described the clinical aspects of the disease, characterized by its etiological agent (Trypanosoma cruzi) and identified its insect vector. Initially, CD occurred only in Latin America and was considered a silent and poorly visible disease. More recently, CD became a neglected worldwide disease with a high morbimortality rate and substantial social impact, emerging as a significant public health threat. In this context, it is crucial to better understand better the epidemiological scenarios of CD and its transmission dynamics, involving people infected and at risk of infection, diversity of the parasite, vector species and T. cruzi reservoirs. Although efforts have been made by endemic and non-endemic countries to control, treat, and interrupt disease transmission, the cure or complete eradication of CD are still topics of great concern and require global attention. Considering the current scenario of CD, also affecting non-endemic places such as Canada, USA, Europe, Australia and Japan, in this review we aim to describe the spread of CD cases worldwide since its discovery until it has become a global public health concern.